Preliminary assessment of the pollution status of Sapang Balen river, Mabalacat city, Philippines - S. Nolasco, Glen; Dave A. Dicuangco , John; S. Arcilla , Marilyn; Edward E. Alfonso , John (SPC Journal of Environmental Sciences, 2024)
Scarcity of freshwater is a significant global threat, particularly in ecosystems like rivers, which are crucial for biodiversity, drinking water, and community sustenance. This study evaluates the ecological health of the Sapang Balen River in Mabalacat City, Pampanga, Philippines, by examining plant species, solid waste accumulation, heavy metals, coliform counts, and physicochemical parameters. Field measurements and laboratory analyses revealed low biodiversity in the river, characterized by many fast-growing and invasive plants that threaten ecosystem balance. Water quality assessments indicate alarmingly high levels of microbial contamination, with coliform counts significantly exceeding safe limits, likely due to urbanization and domestic waste. Despite these challenges, ongoing remediation efforts, such as bioflocculants, filtration systems, and water revetments, show promise for improving water quality. The study highlights the importance of continuous monitoring and adaptive management to restore and sustain the health of the Sapang Balen freshwater ecosystem.